2019
DOI: 10.1249/mss.0000000000001821
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Thermoregulatory Function during Dynamic Exercise in Multiple Sclerosis

Abstract: Introduction Impairments in sudomotor function during passive whole-body heating have been reported in multiple sclerosis (MS), a demyelinating disease of the CNS that disrupts autonomic function. However, the capability of the thermoregulatory system to control body temperature during exercise has never been assessed in MS. Thus, the aim of the present study was to test the hypothesis that thermoregulatory function is impaired in MS patients compared with healthy controls (CON) exercising at simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 32 publications
3
13
0
Order By: Relevance
“…Our collaborative group has recently shown that compared to healthy controls, people with MS demonstrate a blunted sudomotor, but not vasomotor response during moderate intensity exercise at a fixed metabolic H prod (4.5 W•kg -1 ) in a temperate climate (25°C, 30% RH) (1). However, the blunted sweat response with MS was not large enough to alter the rise in rectal and esophageal temperature in that study, possibly due to the relatively cool conditions tested (1). The findings of the present study extend our previous investigations to much hotter conditions (up to T a =35°C).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Our collaborative group has recently shown that compared to healthy controls, people with MS demonstrate a blunted sudomotor, but not vasomotor response during moderate intensity exercise at a fixed metabolic H prod (4.5 W•kg -1 ) in a temperate climate (25°C, 30% RH) (1). However, the blunted sweat response with MS was not large enough to alter the rise in rectal and esophageal temperature in that study, possibly due to the relatively cool conditions tested (1). The findings of the present study extend our previous investigations to much hotter conditions (up to T a =35°C).…”
Section: Discussionsupporting
confidence: 55%
“…It has recently been reported that people with relapsing-remitting MS demonstrate a blunted sudomotor, but not vasomotor response, during moderate exercise at a fixed heat production in a temperate (25°C) environment (1). While this blunted sudomotor response did not result in larger rises in core temperature compared to healthy controls (1), exercise in hotter conditions that approach skin temperature (i.e. 30 to 35˚C) may elicit a net thermal load that exceeds the thermoregulatory capacity of people with MS sufficiently to cause greater rises in body temperature for a given activity level.…”
Section: Introductionmentioning
confidence: 99%
“…Autonomic dysfunction occurs in patients with multiple sclerosis (MS) and can manifest with a range of symptoms including incontinence, urinary retention, gastric and intestinal dysmotility, sexual dysfunction, orthostatic intolerance, vasomotor dysfunction, and sweating and thermoregulatory disorders. [1][2][3][4][5] Demyelination and axonal degeneration affecting the autonomic pathway in the brain stem, hypothalamus, and spinal cord, as well as peripheral autonomic nerve fibers are presumably responsible for such disturbances. Autonomic function tests including urodynamic tests, heart rate responses to deep breathing, Valsalva ratio, sympathetic skin responses, and electrochemical skin conductance are abnormal in patients with MS [5][6][7][8][9] and have been related to the severity of neurologic disability [7][8][9] and lesions detected on brain magnetic resonance imaging (MRI).…”
Section: Introductionmentioning
confidence: 99%
“…33 ► Increases in body and/or environmental temperature (without cooling) can exacerbate neurological symptoms, including fatigue, in those with multiple sclerosis, 34 where the sudomotor response to heating is already impaired. 35 Para Athletics Paratriathlon Heat exhaustion 5 Heat-related illness 5 Heat-related illness 30 Limb deficiency ► Display limited body surface area for evaporative and convective heat loss, increasing heat storage. 36 ► Closer coupling of T c and T sk which is further exacerbated by socket liners and prostheses limiting heat dissipation.…”
Section: Wheelchair Rugby Para Athletics Para Archery Paratriathlonmentioning
confidence: 99%